Joint Power and Channel Allocation for D2D Underlaying Cellular Networks With Rician Fading - Wang, Yinlu; Chen, Ming; Huang, Nuo; Yang, Zhaohui; Pan, Yijin (IEEE communications letters, 2018)
This letter investigates the joint power and channel allocation problem for device-to-device (D2D) underlaying cellular systems over Rician fading D2D channels. We aim at maximizing the sum rate of cellular users (CUEs) subject to the rate constraints for CUEs as well as the outage probability and latency constraints for D2D users (DUEs). The expressions of outage probability and latency for DUEs are derived first. Subsequently, a joint power and channel allocation algorithm is proposed, where the optimal power allocation is derived independently on each sub-channel and the optimal channel allocation scheme is obtained by the Hungarian algorithm. Numerical results verify the analytical analysis and the optimality of the proposed algorithm.